Targeted tumor killing via an intracellular antibody against erbB-2. - Deshane, J (1995)
Specific killing of erbB-2-overexpressing tumor cells can be achieved using expression of an intracellular antibody directed against the erbB-2 oncoprotein. We have developed a strategy using a recombinant adenovirus encoding an anti-erbB-2 single chain antibody to achieve targeted tumor cell killing in vivo and can show significantly prolonged survival of animals carrying a human ovarian carcinoma tumor burden within their peritoneal cavities. This strategy of gene therapy for ovarian carcinoma offers the potential to achieve highly specific, targeted killing of human tumor cells and thus establishes the rationale to undertake human clinical trials on this basis.